قلق المستقبل المهني وعلاقته بالدافعية للتعلم لدى الطلبة المقبلين على التخرج - عيشوش، منال (جامعة الوادي university of Eloued, 2019)
الملخص: وتهدف الدراسة إلى معرفة طبيعة العلاقة التي تربط بين قلق المستقبل المهني والدافعية للتعلم عند الطلبة المقبلين على التخرج وللتأكد من تحقق فرضيات الدراسة، اعتمدت الدراسة على المنهج الوصفي الإرتباطي، وذلك باستخدام مقياسي، قلق المستقبل المهني لإستاذ يونس بن حسين(2017) ودافعية للتعلم ليوسف قطامي(1989) اللذان تم التأكد من خصائصهما السيكومترية(الصدق، الثبات) وبعد جمع البيانات ثم تبويبها ومعالجتها بإستخدام الحزمة الإحصائية(spss) توصلت الدراسة إلى نتائج الآتية: - لا توجد علاقة إرتباطية دالة إحصائياً بين قلق المستقبل المهني والدافعية للتعلم لدى المقبلين على التخرج. - لا توجد فروق ذات دلالة إحصائية في قلق المستقبل المهني تعزى لمتغير الجنس(ذكور/ إناث) - لا توجد فروق ذات دلالة إحصائية في قلق المستقبل المهني تعزى لمتغير التخصص بين (العلوم الإجتماعية / العلوم الدقيقة) - لا توجد فروق ذات دلالة إحصائية في دافعية التعلم تعزى لمتغير الجنس ( ذكور/ إناث) - لا توجد فروق ذات دلالة إحصائية في دافعية التعلم تعزى لمتغير التخصص بين ( العلوم الإجتماعية / العلوم الدقيقة) Résumé :فرنسية أو انجلزية The study aims at finding out the nature of the relationship between the professional future anxiety and the motivation of learning among the students coming to graduate and to ascertain the validity of the hypotheses of the study. The study relied on the descriptive descriptive method, using the measures of the professional future of Yunus Bin Hussein (2017) (1989), which were confirmed by their cytometric characteristics (honesty, persistence). After collecting the data and then classifying and processing them using the statistical package (spss), the study reached the following results: - There is no statistically significant correlative relationship between the professional future and the motivation to learn for those coming to graduate. - There are no statistically significant differences in the professional future concern due to gender variable: male / female. - There are no statistically significant differences in the professional future anxiety due to the specialization variable : social sciences / exact sciences. - There are no statistically significant differences in learning motivation due to sex variable. - There are no statistically significant differences in learning motivation due to specialization variable:Social sciences and exact sciences.
دراسة ميدانية كلية العلوم الإجتماعية وكلية العلوم الدقيقة جامعة الشهيد حمة لخضر بالوادي
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: قلق المستقبل، الدافعية للتعلم; Anxiété future, motivation à apprendre; Future anxiety, motivation to learn